Head pleomorphic sarcoma showing murine double minute 2 amplification without a well‐differentiated liposarcoma component in a pediatric patient. Issue 2 (26th December 2022) - Akaihata, Mitsuko; Takahashi, Ikuko; Kakuda, Yuko; Kawata, Takuya; Mukaigawa, Takashi; Onitsuka, Testuro; Murayama, Shigeyuki; Ishida, Yuji
Abstract: Background: Murine double minute 2 (MDM2) is an oncogene that inhibits p53, leading to decreased apoptosis. Sarcomas showing MDM2 amplification are rare among pediatric patients. Case: A 14‐year‐old boy presented with pleomorphic sarcoma of the head showing MDM2 amplification without a well‐differentiated liposarcoma component. Although chemotherapy was initially performed to reduce the tumor size before surgery, the tumor did not shrink. The patient underwent complete surgical resection. Microscopic examination revealed a positive surgical margin; thus, postoperative proton‐beam radiotherapy was performed. 3 years after the therapy, no sign of recurrence was observed. Conclusion: Macroscopic surgical resection combined with adjuvant postoperative radiotherapy was effective against MDM2‐amplified pleomorphic sarcoma refractory to neoadjuvant chemotherapy in a pediatric patient.